2018
DOI: 10.3892/etm.2018.5993
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in mesenchymal stromal cells: A novel therapeutic strategy for stroke (Review)

Abstract: A stroke is a focal cerebral insult that frequently causes severe neurological deficit and mortality. Recent studies have demonstrated that multipotent mesenchymal stromal cells (MSCs) hold great promise for neurovascular remodeling and neurological function recovery following a stroke. Rather than a direct replacement of parenchymal brain cells, the therapeutic mechanism of MSCs is suggested to be the secretion of soluble factors. Specifically, emerging data described MSCs as being able to release extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 110 publications
0
42
0
4
Order By: Relevance
“…The most common EV markers are ALG-2-interacting protein X (Alix), tetraspanin proteins CD9, CD63, CD81 and heat-shock protein (Hsp)60, Hsp70, and Hsp90. In addition, MSC-released EVs express unique surface antigens including CD44, CD73, CD90 and CD105 [263].…”
Section: Extracellular Vesicles (Exosomes)mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common EV markers are ALG-2-interacting protein X (Alix), tetraspanin proteins CD9, CD63, CD81 and heat-shock protein (Hsp)60, Hsp70, and Hsp90. In addition, MSC-released EVs express unique surface antigens including CD44, CD73, CD90 and CD105 [263].…”
Section: Extracellular Vesicles (Exosomes)mentioning
confidence: 99%
“…They overcome some limitations of MSC-based therapies including allogeneic immune rejection, malignant transformation, and premature cell differentiation. EVs have the unique capability to cross the blood-brain barrier, which is very important in the treatment of neurological disorders [263]. This means that EVs have better advantages in the clinic in the treatment of nervous system diseases as compared to the therapeutic potential of MSCs.…”
Section: Extracellular Vesicles (Exosomes)mentioning
confidence: 99%
“…Recent studies have demonstrated that multipotent mesenchymal stromal cells (MSCs) hold great promise for neurovascular remodeling and neurological function recovery following a stroke. It has been demonstrated that MSC-derived exosomes have a neuroprotective effect against stroke due in part to changing the miRNA profile of exosomes during and after stroke (see [120]).…”
Section: Extracellular Vesicles (Evs) As a Drug Delivery Systemmentioning
confidence: 99%
“…Because of their β1 and α2b integrin-enriched content, human neural stem cell-derived EV administration recovers both tissue and sensorimotor function and may protect the BBB integrity, in the preclinical mouse thromboembolic model of stroke [122,123]. Similarly, multipotent mesenchymal stromal cells (MSCs), through their capacity to secrete soluble factors, play an important role in brain repair.…”
Section: Extracellular Vesicles' Perspective Use In Brain Pathologymentioning
confidence: 99%
“…Similarly, multipotent mesenchymal stromal cells (MSCs), through their capacity to secrete soluble factors, play an important role in brain repair. It was demonstrated that MSC cargos modulate cell signaling in ischemic stroke by PI3K/Akt pathway activation [123,124] and EVs facilitated secretion of miRs sustaining MSC neuroprotective effects in ischemic stroke as well. Previous research demonstrated that intravenous administration of bone marrow-MSCs containing exosomes transferred miR-133b to astrocytes and neurons into the ischemic boundary zone [120,123], and MSCs cultured in the presence of extracts from rat ischemic brain induced increased expression of exosomal miR133b [123,125].…”
Section: Extracellular Vesicles' Perspective Use In Brain Pathologymentioning
confidence: 99%